2014
DOI: 10.3109/17453674.2014.957078
|View full text |Cite
|
Sign up to set email alerts
|

Cam deformity and hip degeneration are common after fixation of a slipped capital femoral epiphysis

Abstract: Background and purpose —Slipped capital femoral epiphysis is thought to result in cam deformity and femoroacetabular impingement. We examined: (1) cam-type deformity, (2) labral degeneration, chondrolabral damage, and osteoarthritic development, and (3) the clinical and patient-reported outcome after fixation of slipped capital femoral epiphysis (SCFE).Methods —We identified 28 patients who were treated with fixation of SCFE from 1991 to 1998. 17 patients with 24 affected hips were willing to participate and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In addition, if a smooth fixation device (such as the Hansson hookpin) is used, the proximal femur will continue to grow in average 7 mm after in situ fixation 6 It was recently shown that the amount of remaining growth of the proximal femur correlates inversely to the reduction of the alpha-angle 31 In other words, the remaining growth will lead to decreased risk of persisting FAI in adulthood. Such remodeling may explain why our patients have relative low alpha angles compared to other studies 25,32,33 . The mean alpha angle in our cohort was 61.5 .…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In addition, if a smooth fixation device (such as the Hansson hookpin) is used, the proximal femur will continue to grow in average 7 mm after in situ fixation 6 It was recently shown that the amount of remaining growth of the proximal femur correlates inversely to the reduction of the alpha-angle 31 In other words, the remaining growth will lead to decreased risk of persisting FAI in adulthood. Such remodeling may explain why our patients have relative low alpha angles compared to other studies 25,32,33 . The mean alpha angle in our cohort was 61.5 .…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies of early cartilage degeneration in the short and mid-term after SCFE are rare. Klit et al 32 and Miese et al investigated 24 respectively 35 SCFE hips 15 and 12 years after slippage and could both verify significantly higher prevalence of chondrolabral damage on structural MRI in hips with pathological alpha angles. Zilkens et al investigated a mix of 28 acute and chronic SCFE hips, at mean age 24 years (range 18e30) using dGEMRIC (1.5 T, 3D sequence).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, pediatric hip disorders can predispose to FAI. SCFE deformities have been shown to predispose to the development of cam impingement in adulthood, which is mechanically consistent with the anterosuperior displacement of the femoral metaphysis in the pediatric disease ( 5 , 19 , 22 , 23 ). Similarly, the natural history of LCPD can lead to FAI, in this case resulting from aspherical enlargement of the femoral head (coxa magna) representing the healed osteonecrotic epiphysis ( 23 25 ).…”
Section: Who Gets Fai?mentioning
confidence: 64%
“…Nötzli et al describe a mean angle alpha of 74° in a group of patients with symptomatic hip impingement and a mean angle alpha of 42° in a control group of healthy volunteers (7). Klit et al report a mean angle alpha of 83° in a group of SCFE patients 15 years after screw fixation (25). In our study population the mean angle alpha of the affected hips at most recent follow up was 62°, the contralateral hips were 45°.…”
Section: Discussionmentioning
confidence: 99%